Parsimony, phylogeny, and genomics - Albert, Victor A. (Victor Anthony), 1964- (Oxford, OX : Oxford University Press, 2005)
'This book examines the potential that parsimony analysis (cladistics) summarization method has for both structural and functional comparative genomic research'--Provided by publisher
Includes bibliographical references (p. 201-217) and index
Keywords: Cladistic analysis; Genetics; Phylogeny